Immunofluorescence microscopy of γH2AX and 53BP1 for analyzing the formation and repair of DNA double-strand breaks - Popp, Henning; Brendel, Susanne; Hofmann, Wolf-Karsten; Fabarius, Alice (JoVE. Video journal, 2017)
DNA double-strand breaks (DSB) are serious DNA lesions. Analysis of the formation and repair of DSB is relevant in a broad spectrum of research areas including genome integrity, genotoxicity, radiation biology, aging, cancer, and drug development. In response to DSB, the histone H2AX is phosphorylated at Serine 139 in a region of several megabase pairs forming discrete nuclear foci detectable by immunofluorescence microscopy. In addition, 53BP1 (p53 binding protein 1) is another important DSB-responsive protein promoting repair of DSB by nonhomologous end-joining while preventing homologous recombination. According to the specific functions of γH2AX and 53BP1, the combined analysis of γH2AX and 53BP1 by immunofluorescence microscopy may be a reasonable approach for a detailed analysis of DSB. This manuscript provides a step-by-step protocol supplemented with methodical notes for performing the technique. Specifically, the influence of the cell cycle on γH2AX foci patterns is demonstrated in normal fibroblasts of the cell line NHDF. Further, the value of the γH2AX foci as a biomarker is depicted in x-ray irradiated lymphocytes of a healthy individual. Finally, genetic instability is investigated in CD34+ cells of a patient with acute myeloid leukemia by immunofluorescence microscopy of γH2AX and 53BP1.